2011
DOI: 10.1007/s11064-011-0646-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Placental Growth Factor in Cerebrospinal Fluid of Patients with Epilepsy

Abstract: Recent studies suggest that angiogenesis and vascular endothelial growth factor (VEGF) are involved in the pathophysiology of epilepsy. However, relatively little data are available linking placenta growth factor (PIGF) with epilepsy. In this study, we assessed concentrations of PIGF in cerebrospinal fluid (CSF) of 60 epileptic patients and 24 non-seizure subjects using sandwich enzyme-linked immunosorbent assays. Epileptic patients in general had higher concentration of CSF-PIGF than controls (7.95 ± 0.88 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, although sFlt was also elevated as expected in the PE-PTZ group, PlGF in this group was paradoxically not decreased. By way of explanation of this result, it has been shown previously by Xu et al [43] in a case control study that PlGF is elevated in the cerebral spinal fluid of epileptic patients compared with non-seizure subjects. This suggests that PlGF may be increased as a consequence of seizure activity.…”
Section: Discussionmentioning
confidence: 58%
“…However, although sFlt was also elevated as expected in the PE-PTZ group, PlGF in this group was paradoxically not decreased. By way of explanation of this result, it has been shown previously by Xu et al [43] in a case control study that PlGF is elevated in the cerebral spinal fluid of epileptic patients compared with non-seizure subjects. This suggests that PlGF may be increased as a consequence of seizure activity.…”
Section: Discussionmentioning
confidence: 58%
“…In accordance with the evidence of a protective function of CX3CL1, patients with mild cognitive impairment (MCI), a clinical condition that often precedes AD, have higher circulating levels of CX3CL1 in comparison with AD patients; and the level of CX3CL1 is inversely correlated to AD severity . CX3CL1 could also play an important protective role in human epilepsy, as shown by studies that reported increased levels of CX3CL1 in the CSF of patients with mesial temporal lobe epilepsy (MTLE) and increased CX3CL1 and CX3CR1 expression in brain tissue from MTLE patients . Electrophysiological recordings in freshly resected human brain slices from MTLE patients evidenced the ability of CX3CL1 to reduce the use‐dependent decrease of GABA‐evoked currents, possibly limiting the deregulation of excitatory neurotransmission that underlies SE‐induced neuronal damage …”
Section: Translation To Human Brain Diseasesmentioning
confidence: 69%
“…Recent evidence suggests that CX3CL1/CX3CR1 signaling also plays a role in cell death associated with epilepsy; in particular, the expression of CX3CR1 was shown to be increased in the hippocampus of adult rats one week following status epilepticus (SE); and intracerebroventricular injection of an anti‐CX3CR1 antibody diminished SE‐induced microglial activation and neurodegeneration …”
Section: Neurotoxic Profile Of Cx3cl1mentioning
confidence: 99%
“…In adult human brain, PGF is expressed in neurons but not glial cells (Xu et al, 2012a). PGF was increased in human cerebrospinal fluid after seizures (Xu et al, 2012b) suggesting PGF has an important neuroprotective, homeostatic role. Neuroprotection could be due to improved neoangiogenesis, (Gaál et al, 2013) to direct effects on neural cells or to combined effects.…”
Section: Left Common Carotid Artery Ligation (Lcca)mentioning
confidence: 99%